Spiritual Health and Resilience Among University Students: the Mediating Role of Self-Esteem - Borji, Mitra (Pastoral psychology, 2020)
Due to the positive effects of resilience on different dimensions of health, the aim of this study was to propose and examine a model for a deeper understanding of the predictive factors of resilience. In this hypothetical model, self-esteem was suggested as the mediator of the relationship between spiritual health and resilience. This correlational design's statistical sample consisted of 240 university students who were chosen via multilevel cluster sampling from different faculties of Iran University of Medical Sciences in 2018. For data collecting, the Spiritual Health Questionnaire, Coopersmith Self-Esteem Inventory, and the Connor-Davidson Resilience Scale were utilized, and for data analysis, the Pearson correlation method and structural equation modeling were calculated using SPSS 18 and LISREL 8.5 software. According to the results of the current study, self-esteem played a partially mediating role in the relation between spiritual health and resilience. The fitness indices demonstrated satisfying fitness of the model. Since spiritual and religious beliefs are important topics in the lives of the people of Iran, it is possible to strengthen the field of self-esteem and resilience through education on spirituality and increase their positive attitudes toward life.